Oral contraceptive pill (OCP) treatment alters the gene expression of intercellular adhesion molecule-1 (ICAM-1), tumor necrosis factor-α (TNF-α), monocyte chemoattractant protein-1 (MCP-1) and plasminogen activator inhibitor-1 (PAI-1) in polycystic ovary syndrome (PCOS) women compared to drug-naive PCOS women - Yousuf, Syed Douhath; Ganie, Mohammad Ashraf; Urwat, Uneeb; Andrabi, Syed Mudasir; Zargar, Mohammad Afzal; Dar, Mashooq Ahmad; Manzoor-ul-Rehman, Mir; Mudassar, Syed; Rashid, Fouzia (BMC women's health, 2023)
Polycystic ovary syndrome (PCOS) presents clinical symptoms of menstrual abnormalities, excessive hair growth (hirsutism), scalp hair loss, acne and infertility. Metabolic abnormalities such as obesity, insulin resistance, glucose intolerance and cardiovascular problems constitute an essential part of PCOS, all of which can have significant long-term health consequences. Low-grade chronic inflammation demonstrated by persistent moderately elevated serum levels of inflammatory and coagulatory markers plays a critical role in the pathogenesis of PCOS. Oral contraceptive pills (OCPs) constitute the mainstay of pharmacologic therapy for women with PCOS to regularize cyclicity and ameliorate androgen excess. On the other hand, OCP use is associated with various venous thromboembolic and proinflammatory events in the general population. PCOS women always carriers the increased lifetime risk of these events. The studies on the effect of OCPs on inflammatory, coagulation and metabolic parameters in PCOS are less robust. Therefore in this study, we investigated and compared the messenger RNA (mRNA) expression profiles of genes implicated in inflammatory and coagulation pathways between drug-naive and OCP-treated PCOS women. The selected genes include intercellular adhesion molecule-1 (ICAM-1), tumor necrosis factor-α (TNF-α), monocyte chemoattractant protein-1 (MCP-1) and plasminogen activator inhibitor-1 (PAI-1). Furthermore, the correlation between the selected markers and various metabolic indices in the OCP group has also been explored. The relative amounts of ICAM-1, TNF-α, MCP-1 and PAI-1 mRNA in peripheral blood mononuclear cells from 25 drug-naive PCOS subjects (controls) and 25 PCOS subjects who received OCPs containing 0.03 mg-ethinyl-estradiol and 0.15 mg-levonorgestrel for at least six months (cases) were estimated using real-time qPCR. The statistical interpretation was conducted using SPSS version 20.0 (SPSS, Inc, Chicago, IL), Epi Info version 2002 (Disease Control and Prevention Centres, Atlanta, GA) and GraphPad Prism 5 (GraphPad Software, La Jolla, CA) software. Six months of OCP therapy enhanced the expression of inflammatory genes viz ICAM-1, TNF-α and MCP-1 mRNA in PCOS women by 2.54, 2.05 and 1.74 folds, respectively, in this study. However, PAI-1 mRNA in the OCP group showed no significant increase. Furthermore, in cases, ICAM-1 mRNA expression positively correlated with body mass index (BMI) (p = 0.01), fasting insulin (p = 0.01), insulin 2 h p = 0.02), glucose 2 h (p = 0.01) and triglycerides (p = 0.01). TNF-α mRNA expression positively correlated with fasting insulin (p = 0.0007). MCP-1 mRNA expression positively correlated with (BMI) (p = 0.002). OCPs helped reduce clinical hyperandrogenism and regularise menstrual cycles in women with PCOS. However, OCP use was associated with increased fold expression of inflammatory markers which positively correlated with metabolic abnormalities.